2006
DOI: 10.1024/0369-8394.95.34.1275
|View full text |Cite
|
Sign up to set email alerts
|

Risikoklassifikationen bei Leberzirrhose

Abstract: Prognostic models are useful in estimating disease severity and survivial and are used to make decisions regarding specific medical interventions. These models are developed using analytical methods that involve determining the effects of variables of interest (eg, laboratory values) on specific outcomes such as death. There are two models that are used commonly in the care of patients witch chronic liver disease: the Child-Pugh score and the recently described Model for End-Stage Liver Disease (MELD). MELD sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Strahl and Maier found that the synthetic function of the liver is reflected by the levels of serum cholinesterase, which is synthesized by hepatocytes . 9 The cirrhotic patients were strictly grouped into the A, B, and C groups based on their Child-Pugh scores. The highest numbers of patients were in Child Class B (40%).…”
Section: Resultsmentioning
confidence: 99%
“…Strahl and Maier found that the synthetic function of the liver is reflected by the levels of serum cholinesterase, which is synthesized by hepatocytes . 9 The cirrhotic patients were strictly grouped into the A, B, and C groups based on their Child-Pugh scores. The highest numbers of patients were in Child Class B (40%).…”
Section: Resultsmentioning
confidence: 99%